Characterization of the antagonistic potential of the glyphosate-tolerant Pseudomonas resinovorans SZMC 25872 strain against the plant pathogenic bacterium Agrobacterium tumefaciens - Zhumakayev, Anuar R.; Varga, Mónika; Vörös, Mónika; Kocsubé, Sándor; Ramteke, Pramod W.; Szekeres, András; Vágvölgyi, Csaba; Hatvani, Lóránt; Marik, Tamás (Frontiers in Plant Science, 2022)
The utilization of microorganisms with biocontrol activity against fungal and bacterial pathogens of plants is recognized as a promising, effective, and environment-friendly strategy to protect agricultural crops. We report the glyphosate-tolerant Pseudomonas resinovorans SZMC 25872 isolate as a novel strain with antagonistic potential towards the plant pathogenic bacterium Agrobacterium tumefaciens. In our studies, the growth of the P. resinovorans SZMC 25872 and A. tumefaciens SZMC 14557 isolates in the presence of 74 different carbon sources, and the effect of 11 carbon sources utilized by both strains on the biocontrol efficacy was examined. Seven variations of media with different carbon sources were selected for the assays to observe the biocontrol potential of the P. resinovorans strain. Also, 50% concentrations of the cell-free culture filtrates (CCF) obtained from medium amended with L-alanine or succinic acid as sole carbon source were found to be effective for the growth suppression of A. tumefaciens by 83.03 and 56.80%, respectively. The effect of 7 media on siderophore amount and the activity of extracellular trypsin- and chymotrypsin-like proteases, as well as esterases were also evaluated. Significant positive correlation was found between the siderophore amount and the percentage of inhibition, and the inhibitory effect of the CCFs obtained from medium amended with succinic acid was eliminated in the presence of an additional iron source, suggesting that siderophores produced by P. resinovorans play an important role in its antagonistic potential. The metabolic profile analysis of the P. resinovorans SZMC 25872 strain, performed by high performance liquid chromatography - high resolution mass spectrometry (HPLC-HRMS), has identified several previously not reported metabolites that might play role in the antagonistic effect against A. tumefaciens. Based on our findings we suggest that the possible inhibition modes of A. tumefaciens SZMC 14557 by P. resinovorans SZMC 25872 include siderophore-mediated suppression, extracellular enzyme activities and novel bioactive metabolites.